Effectiveness Of Simulation-Based Training In Paramedic Education (The Review of Diabetic Studies, 2025)
Introduction: Simulation-based training has gained popularity as an educational strategy in medical education, simulation creates a low-risk environment for patients and participants and allows experiential learning. While the research on effectiveness of simulation-based training is growing, the evidence remains limited in quality and quantity..Aim: To review and discuss the effectiveness of simulation-based training in medical education.Materials and Methods: A literature search was conducted using the PRISMA guidelines, which covered databases such as MEDLINE, EMBASE, CINAHL, and Cochrane Library. Eligibility criteria included English studies published between 2021 and 2025. Study designs were heterogeneous and had quantitative, qualitative, and mixed-methods projects. The specific populations included paramedics and emergency medical health providers. The outcomes of interest focused on clinical skills acquisition and retention.Results: Initial searching yielded 1305 records, of which 25 remained after initial title and abstract reading. Following secondary full-text screening, 11 articles were deemed appropriate for final inclusion. Across all the literature, a range of concepts are discussed: Skill vs Scenario, Virtual Learning, Inter-Professional Learning, Fidelity, Cost, Equipment, Improvement of Competency, Patient Safety, Perception of Simulation.Conclusion: Paramedics provide critically important, often lifesaving, pre hospital care. However, the opportunities to enhance their skills are limited by several factors, most notably their undergraduate and certificate educational requirements, which are much shorter than many other allied health professions. Hence, paramedics rely on simulation-based training more than other clinical disciplines in allied health.